Safety issues with bisphosphonate therapy for osteoporosis. - Suresh, E; Pazianas, M; Abrahamsen, B (2014)
Randomized controlled trials have demonstrated the efficacy of bisphosphonates (BP) in improving BMD and reducing fracture risk. Various safety issues that were not noted in clinical trials have, however, now emerged with post-marketing surveillance and increasing clinical experience. The risk of atypical femoral fracture could increase with long-term use of BP, although absolute risk is very small, particularly when balanced against benefits. A drug holiday should be considered after 5 years of treatment for patients at low risk of fracture, although there is no official recommendation regarding this to guide clinicians. Osteonecrosis of the jaw from low-dose BP used for osteoporosis is very rare, and mainly a complication with high-dose i.v. BP used in oncology. The risk of atrial fibrillation too is negligible, and a definite link cannot be established between BP and oesophageal cancer. BP should be avoided in patients with severe renal impairment and during pregnancy and lactation because of limited safety data. Further epidemiological and clinical data are required to establish safety of BP in long-term users (>5 years) and provide evidence-based management.